Environmental Radiocesium in Subarctic and Arctic Alaska Following Chernobyl - Baskaran, M.; Kelley, J.J.; Naidu, A.S.; Holleman, D.F. (ARCTIC, 1991)
Radiocesium (134Cs and 137Cs) concentrations were measured in soil, plant and wildlife samples from subarctic to arctic Alaska. Concentrations of 137Cs ranged from below detectable or low levels in whale and fish samples to as high as 242 Bq/kg in lichen. For all potential human food items, the radiocesium concentrations measured in this study were below accepted permissible levels for human consumption. Chernobyl-derived radiocesium concentrations ranged from below detectable or low levels in all arctic samples (soil, sediment, lichen, whale, fish and caribou) to 32 Bq/kg in subarctic moss. Therefore the distribution and subsequent deposition of Chernobyl-derived radiocesium appears to be variable but decreasing significantly from the Subarctic (Fairbanks) to the Arctic. The present data support the suggestion that Chernobyl-derived debris arrived from western Canada into central Alaska and subsequently moved to the north (arctic) and to the west, decreasing in the quantity deposited as the debris transversed the state.Key words: Chemobyl, radiocesium, lichen, mushroom, caribou, reindeer, soil, fallout, deposition Mots clés: Chernobyl, césium radioactif, lichen, champignon, caribou, renne, sol, retombées, dépôt